Amartya Sen, leitor de Adam Smith - Luiz Henrique Pacheco (2016)
The work is divided into two main chapters. The first deals with the different interpretations of Adam Smith's works. It is argued that these interpretations varied over the time. Initially seen as an acclaimed moral philosopher, Smith came to be read as an advocate of self-interest. In the 1970s, the publication of the Glasgow Edition of the works and correspondence of Smith led to a renewed interest in Smiths works, which gave rise to new interpretations, now conventionally called the "new readings". These new readings include the work of the Indian economist Amartya Sen, which since the late 1970s devoted himself to the interpretation and dissemination of Smithean ideas. Sens interpretation of Smith's works is the subject of the second chapter of this dissertation. Sen seeks to counter the distortions made by the interpretations of Smiths ideas inspired by mainstream economics. At the same time, Smith's ideas were important to the formulation of Sens approach to the rationality and to the development of Sens capabilities approach.